XPR1 promotes ovarian cancer growth and regulates MHC-I through autophagy - Hui Wang; Xiaodong Luo; Bo Yang; Furong Tang; Xingwei Jiang; Hongtao Zhu; Jianguo Hu (Genes and Diseases, 2025)
Immune checkpoint inhibitors have a poor effect in treating ovarian cancer, and the specific mechanism is unknown. The purpose of this research was to investigate the impact of XPR1 on controlling autophagy in ovarian cancer. The findings suggested an increase in XPR1 expression in ovarian cancer tissues. The elevated level of its expression was linked to the stage of ovarian cancer, as well as overall survival and progression-free survival. XPR1 enhanced the growth and spread of ovarian cancer while suppressing autophagy. Moreover, XPR1 suppressed autophagy flux by interacting with LAMP1 and the PI3K/Akt/mTOR pathway. XPR1 controlled the positioning and production of MHC-I molecules on the surfaces of ovarian cancer cells via autophagy. Silencing XPR1 combined with the autophagy inhibitor chloroquine significantly inhibited tumor growth in mouse ovarian cancer models. In conclusion, the findings indicate that XPR1 could serve as a promising target for the diagnosis and treatment of ovarian cancer. Combined autophagy inhibitors may improve the sensitivity of ovarian cancer immunotherapy.